Suitability and Biophysical Characteristics of Sustainable Food Agricultural Land in Aceh Singkil - Muhammad Yasar; Syahrul Syahrul; Zulfa Fijannah; Nor Diana Mohd Idris (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2022)
Abstract: Identification of the suitable and biophysical characteristics of land is crucial to meeting sustainable food production both locally and globally. This study aims to examine the suitability of paddy land and classify land quality based on the biophysical characteristics of paddy fields designated as sustainable food fields in Aceh Singkil District, Indonesia. The qualitative technique is through observation and soil sampling in the field from five sub-districts with the highest level of land availability, namely: Danau Paris, Simpang Kanan, Suro Makmur, Kuta Baharu, and Gunung Meriah. Soil sample testing was carried out in the laboratory, and the records received were analyzed for the use of the Matching Method as a means of evaluating the traits of the land inside the Land Use Unit (SPL). The results of the analysis are visualized using a Geographic Information System (GIS) approach. We found that, based on suitable characteristics, land can be improved by improving the limiting factors, while biophysical characteristics can be improved by increasing land suitability. The subdistricts of Danau Paris, Simpang Kanan and Kuta Baharu are included in the category of the first primary paddy land. The land category must be protected, preserved, and designated as LP2B, while Suro Makmur and Gunung Meriah Subdistricts are included in the category of the first secondary paddy land that requires improvement efforts to improve its biophysical condition. The first primary paddy land is the land that has technical or semi-technical irrigation status with a cropping index (IP) ≥ 2 and productivity ≥ 4.50. Whereas the first secondary paddy land is the land that has technical or semi-technical irrigation status with a cropping index (IP) ≥ 2, but productivity ≤ 4.50. Both of them should be zoned as protected areas. Abstract: Identifikasi karakteristik dan biofisik lahan yang sesuai sangat penting untuk memenuhi produksi pangan berkelanjutan baik secara lokal maupun global. Penelitian ini bertujuan untuk mengkaji kesesuaian lahan sawah dan mengklasifikasikan kualitas lahan berdasarkan karakteristik biofisik lahan sawah yang ditetapkan sebagai lahan pangan berkelanjutan di Kabupaten Aceh Singkil, Indonesia. Metode yang digunakan adalah kualitatif melalui observasi dan pengambilan sampel tanah di lapangan dari 5 (lima) kecamatan dengan tingkat ketersediaan lahan tertinggi yaitu: Danau Paris, Simpang Kanan, Suro Makmur, Kuta Baharu, dan Gunung Meriah. Pengujian sampel tanah dilakukan di laboratorium dan data yang diperoleh dianalisis dengan menggunakan Metode Matching dengan cara mengevaluasi sifat-sifat tanah dalam Satuan Penggunaan Tanah (SPL). Hasil analisis divisualisasikan dengan menggunakan aplikasi Sistem Informasi Geografis (SIG). Hasil penelitian menunjukkan bahwa berdasarkan karakteristik yang sesuai, lahan dapat diperbaiki melalui perbaikan faktor pembatas, sedangkan karakteristik biofisik dapat ditingkatkan melalui peningkatan kesesuaian lahan. Kecamatan Danau Paris, Simpang Kanan dan Kuta Baharu masuk dalam kategori lahan persawahan primer ke-1, kategori lahan harus dilindungi dan dilestarikan serta ditetapkan sebagai LP2B, sedangkan Kecamatan Suro Makmur dan Gunung Meriah masuk dalam kategori ke-1. lahan sawah sekunder yang memerlukan upaya perbaikan untuk memperbaiki kondisi biofisiknya. Lahan sawah primer ke-1 adalah lahan yang berstatus irigasi Teknis atau Semi Teknis dengan indeks tanam (IP) ≥ 2 dan produktivitas ≥ 4,50. Sedangkan lahan sawah sekunder ke-1 adalah lahan yang berstatus irigasi Teknis atau Semi Teknis dengan indeks tanam (IP) ≥ 2, namun produktivitas ≤ 4,50. Keduanya harus dijadikan kawasan lindung.